Applicability of the AHA/ACC/HRS guideline for implantable cardioverter defibrillator implantation in Japanese patients with cardiac sarcoidosis. (14th October 2021) - Takenaka, S; Kobayashi, Y; Nagai, T; Kato, Y; Komoriyama, H; Nagano, N; Kamiya, K; Konishi, T; Sato, T; Omote, K; Tada, A; Iwano, H; et al.
Abstract: Background: Sarcoidosis is a systemic granulomatous disease that affects multiple organs. Cardiac involvement is a key determinant of poor clinical outcomes in the patients with sarcoidosis, as it causes congestive heart failure, conduction abnormalities, ventricular tachycardia and fibrillation (VT/VF), and sudden cardiac death (SCD). Although implantable cardioverter defibrillators (ICDs) are used to prevent SCD from VT/VF in patients with cardiac sarcoidosis (CS), the generalizability of the AHA/ACC/HRS guidelines for the Japanese CS patients remains unclear. Purpose: We aimed to assess, among Japanese patients with CS, the ICD recommendations from the 2017 AHA/ACC/HRS Guidelines for Management of Patients with Ventricular Arrhythmias and the Prevention of Sudden Cardiac Death. Methods: We examined 188 consecutive patients with CS in two tertiary hospitals between 1979 and 2020. The primary outcome was defined as a composite outcome involving SCD or ventricular arrhythmic events. Ventricular arrhythmic events were defined as either emergency treatment for VF or sustained VT, which included appropriate ICD therapy. Results: During a median follow-up period of 5.68 (IQR: 4.87–6.70) years, the primary outcome occurred in 44 patients (23%), which included 6 cases of SCD and 38 cases of VT/VF. ICD implant was indicated based on left ventricular ejection fraction (LVEF) of ≤35% (class I recommendation) in 62 patients, with an annualized event rate of 3.93%. A LVEF of >35% with a need for a permanent pacemaker (class IIa recommendation) was observed for 53 patients, with an annualized event rate of 2.54%. A LVEF of >35% with late gadolinium enhancement (LGE) during cardiovascular magnetic resonance (class IIa recommendation) was observed for 62 patients, with an annualized event rate of 2.38% (Figure A). Kaplan-Meier analyses revealed that patients with a class I recommendation for ICD implantation had a significant higher incidence of the primary outcome, compared to patients with a class IIa recommendation and patients with no indication for ICD implantation (P=0.03). However, there were no significant differences in the incidence of the primary outcome between patients with a LVEF of >35% and a need for a permanent pacemaker and patients with a class I recommendation (P=0.08) or patients with a LVEF of ≤35% (P=0.31). Moreover, there was no significant difference in the incidence of the primary outcome between patients with a LVEF of >35% and LGE on cardiovascular magnetic resonance and patients with a class I recommendation (P=0.054) or patients with a LVEF of ≤35% (P=0.22) (Figure B). Conclusions: The American guideline recommendations for ICD implantation might be applicable to Japanese patients with CS. Implantation of an ICD may need to be considered in these patients if they require a permanent pacemaker or have LGE, regardless of LVEF. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Japan Society for the Promotion of Science